Rural Tourism Contributions to Rural Development in the Eastern Black Sea Region of Turkey - Boz, Ismet; Kilic, Osman; Kaynakci, Cevahir (International Journal of Scientific Research and Management (IJSRM), 2018)
Rural tourism is considered as one of the essential elements making significant contributions to rural development in many developing countries. A well planned and adequately operated rural tourism sector provides job opportunities for local people, increases living standards, alleviates poverty, prevents migration, and ultimately makes it possible for rural people to enjoy living at their original places of residencies. All of these benefits encourage governments and all other relevant stakeholders to put more emphasis on rural tourism activities when planning and to implement rural development programs. The primary aim of this study was to examine the opportunities of sustainable rural tourism in the Eastern Black Sea Region of Turkey. It based on an extensive review of related literature, governmental reports, and experiences and observations of the researchers in the region. The study revealed that the Eastern Black Sea region has a remarkable rural tourism potential and it will make significant contributions to rural development in Turkey. Particularly highlands, thermal hotels, rural activities, farms, and agribusiness are increasingly attracting many domestic and international tourists in every passing year. However, environmental dimension of rural tourism is under risk because of unplanned housing and road constructions which put more pressure on agricultural lands and rural landscape. For this reason, it is important to consider economic, social, and environmental dimensions of sustainability when preparing and implementing rural tourism programs for the region.